The Impact of Dementia's Affiliate Stigma on the Mental Health of Relatives: A Cross Section Survey - Van den Bossche, Pauline; Schoenmakers, Birgitte (Frontiers in Psychology, 2022)
Objective To determine the impact of the affiliate stigma on mental wellbeing of relatives caring for a person with dementia Design The study was conducted in a cross sectional design Setting The study was conducted in a public setting, addressing relatives caring for a person with dementia Participants Participants were relatives of patients with a formal diagnosis of dementia. Relatives were defined as caring or living closely to a patient. Participants were recruited with the help of care and welfare organisations. Outcome measures The main outcome measure was the impact of the affiliate stigma on mental wellbeing of caring relatives. Results 228 participants fully completed the survey. Women, relatives with a higher education and partners were experienced more impact of the affiliate stigma on mental wellbeing than man, relatives with a lower education and relatives with another relationship to the person with dementia (resp. F-ratio 15.67; p 0.0001; F-ratio 2.5865; p 0.0381; F-ratio 3.1131; p 0.0099). The duration of dementia had a clear significant effect on affiliate stigma (F-ratio 4.9104; p 0.0083) Conclusions Women, partners and relatives with a higher education are more prone to impact of the affiliate stigma on well being. In addition, the longer the diagnosis of dementia exists, the higher the affiliate stigma. Education about dementia and the impact on patients, relatives and the broader social context might alter the taboo surrounding dementia.